Physicochemical, Microbiologically Nutritional and Sensory Evaluation of Ogi (A Traditonal Cereal Based Beverage in Nigeria) Produced from Two Varieties of Sorghum - Temilade, Ozabor Praise; Festus, Fadahunsi Ilesanmi; Oluwabunmi, Adepeju Adekemi (The International Journal of Biotechnology, 2020)
Ogi is a traditional fermented cereal based beverage popularly consumed as weaning food. Therefore, there is need to investigate the physicochemical parameters, microorganisms involved, proximate and sensory analyses associated with its production. Two varieties of sorghum (Brown and White respectively) were collected inside sterile containers from Bodija market in Ibadan, Oyo State, Nigeria. Temperature, pH, titratable acidity, microorganisms involved in fermentation, moisture, ash, protein, fat, crude fibre and carbohydrate contents as well as sensory properties were determined using standard methods. The results showed that pH values decreased with simultaneous increase in titratable acidity during fermentation. Temperature, pH and titratable acidity ranged from: 280C to 300C, 4.02 to 6.25 and 0.05 to 1.53 respectively. Fermentation increased moisture, protein, fat and carbohydrate contents significantly at p≤ 0.05 while ash and crude fibre decreased significantly at p≤ 0.05. Sensory analyses were found within the acceptable ranges according to standard procedures. Lactic acid bacteria was found to be the predominant microorganism involved in the fermentation process which confirms the keeping quality of ogi produced from the two sorghum varieties. The two sorghum varieties (Brown and White) showed to serve as a good weaning food for infants but brown sorghum ogi seems to be more nutritious. Furthermore, the sorghum varieties can be malted during process to reduce bulkiness.